Graduating midwifery students’ preferred model of practice and first job decisions: A qualitative study - Kuliukas, Lesley; Bayes, S.; Geraghty, S.; Bradfield, Zoe; Davison, C. (Elsevier, 2020)
© 2020 Australian College of Midwives